Porous carbons : syntheses and applications - Inagaki, Michio (Elsevier, 2021)
Carbon materials form pores ranging in size and morphology, from micropores of less than 1nm, to macropores of more than 50nm, and from channel-like spaces with homogenous diameters in carbon nanotubes, to round spaces in various fullerene cages, including irregularly-shaped pores in polycrystalline carbon materials. The large quantity and rapid rate of absorption of various molecules made possible by these attributes of carbon materials are now used in the storage of foreign atoms and ions for energy storage, conversion and adsorption, and for environmental remediation. Porous Carbons: Syntheses and Applications focuses on the fabrication and application of porous carbons. It considers fabrication at three scales: micropores, mesopores, and macropores. Carbon foams, sponges, and 3D-structured carbons are detailed. The title presents applications in four key areas: energy storage, energy conversion, energy adsorption, including batteries, supercapacitors, and fuel cells and environmental remediation, emphasizing the importance of pore structures at the three scales, and the diffusion and storage of various ions and molecules. The book presents a short history of each technique and material, and assesses advantages and disadvantages. This focused book provides researchers with a comprehensive understanding of both pioneering and current synthesis techniques for porous carbons, and their modern applications.